LEGAL STATUS OF PETS AND PRETIUM AFFECTIONIS - Srdjan (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
In theory of Law, as well as in legal procedure of Republic of Serbia, widely accepted view is that animals are legal objects – living movable objects in context of Property Law and objects which increases the risk of damage in context of Law of Obligation. However, both views were seriously challenged when Law of Animal Welfare, as well as the amendments in Criminal Law, were incorporated in legal system of Republic of Serbia. Moreover, for the first time solid base is created by these norms to think of animals as very particular subjects of Law. Current legal status of animals – this also refers to pets as a special legal category of animals which is in the focus in this paper – is debatable. However, the very hint of possibility to finally overcome traditional concept “animal = object” creates obligation for us to review all other Civil Law settings and principles de lege lata, and especially de lege ferenda. To be more precise, using the advantages of, both analytical and normative method and techniques that are integral parts of these methods, author reexamines the possibility of compensation of so called pretium affections in case of death or injury of the pet in context of current systematics defined by Law of Obligation and systematics defined by Draft of Civil Code of Republic of Serbia.